Some thermal characteristics of a mineral mixture of palygorskite, metahalloysite, magnesite and dolomite - BAYRAM, HALE (Springer Netherlands, 2007)
An industrial raw material taken from Sivrihisar (Eskişehir, Turkey) region was heat-treated at different temperatures in the range of 100-1000°C for 2 h. The volumetric percentage of the particles having a diameter below 2 μm after staying in an aqueous suspension of the material was determined as 67% by the particle size distribution analysis. The mineralogical composition of the material was obtained as mass% of 32% palygorskite, 10% metahalloysite, 35% magnesite, 20% dolomite and 3% interparticle water by using the acid treatment, X-ray diffraction and thermal analysis (TG, DTA) data. The temperature ranges were determined for the endothermic dehydrations for the interparticle water as 25-140°C, for the zeolitic water as 140-320°C, and for the bound water as 320-480°C, in the palygorskite. The temperature range for the endothermic dehydroxylation and exothermic recrystalization of the palygorskite is 780-840°C. The temperature range for the endothermic dehydroxylation of the metahalloysite and calcinations of magnesite are coincided at 480-600°C. Dolomite calcined in the temperature range of 600-1000°C by two steps. The zig-zag changes in the specific surface area (S/m 2 g -1 ) and specific micro and mesopore volume (V/cm 3 g -1 ) as the temperature increases were discussed according to the dehydrations in the palygorkskite, dehydroxylation of palygorskite and metahalloysite, and calcinations in magnesite and dolomite. © 2007 Springer Science+Business Media LLC.
Keywords: Dehdyration; Dehydroxylation; Metahalloysite; Palygorskite; Thermal analysis; XRD